Residential greenness and increased physical activity in patients after coronary artery bypass graft surgery. (3rd December 2019) - Sadeh, Maya; Brauer, Michael; Chudnovsky, Alexandra; Ziv, Arnona; Dankner, Rachel
Abstract: Aims: Physical activity is a fundamental component of rehabilitation following coronary artery bypass (CABG) surgery. Proximity to neighbourhood green spaces may encourage physical activity. We investigated the association between residential greenness and exercise-related physical activity post-CABG surgery. Methods: Participants in a prospective cohort study of 846 patients (78% men) who underwent CABG surgery at seven cardiothoracic units during the time period 2004–2007 were interviewed regarding their physical activity habits one day before and one year after surgery. Exposure to residential neighbourhood greenness (within a 300 m buffer around their place of residence) was measured using the Normalized Difference Vegetative Index. Participation in exercise-related physical activity (yes/no), weekly duration of exercise-related physical activity and the change in exercise-related physical activity between baseline and follow-up were examined for associations with residential greenness, adjusting for socio-demographic factors, propensity score adjusted participation in cardiac rehabilitation and health-related covariates after multiple imputation for missing variables. Results: Living in a higher quartile of residential greenness was associated with a 52% greater odds of being physically active (OR 1.52, 95% CI 1.22–1.90). This association persisted only (OR 1.75, 95% CI 1.35–2.27) among patients who did not participate in cardiac rehabilitation following surgery and was stronger in women (OR 2.38, 95% CI 1.40–4.07) than in men (OR 1.37, 95% CI 1.07–1.75). Participants who lived in greener areas were more likely to increase their post-surgical physical activity than those who lived in less green areas (OR 1.59, 95% CI 1.25–2.01). Conclusions: Residential greenness appears to be beneficial in increasing exercise-related physical activity in cardiac patients, especially those not particpating in cardiac rehabilitation after CABG surgery.